PEDAGOGICAL VIEWS OF ABU NASR FAROBI (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Abstract: this article provides information on the life path of Abu Nasr Farabi, various information related to the science of pedagogy and thoughts on education, about the great contributions of Farabi to science.